Perilaku Waria (Studi Kasus Remaja) di Mandailing Natal - Nurhasanah Pardede; Asmaryadi Asmaryadi (Analitika: Jurnal Magister Psikologi UMA, 2018)
This aims of this research is to reveal the pattern behavior of transgenders in Siabu Sub-District, Mandailing Natal District. Factors that caused the behavior, motivation that drives the behavior and father's involvement in eduation is among the matters that revelaed by this study. This study uses qualitative deskriptif methods with a snowball sampling case study approach. Subjects participated in this study four were transgender behaviour of adolescents in simangambat village Siabu Sub- district Mandailing Natal District. Data collection techniques through observation, interviews and documentation. The results of the study showed that the behaviour patterns of tranvestites in siabu village during the day  were male working as salon employees, operating at night with female appearance wear tight clothes, make their faces up, sexy and fragrant, dating men,  some of them are tempted, have an intimate relation through buttocks, jealousy between each transvestite in seizing men, factors causing the emergence of transgender behaviour in siabu sub district are saused by psychological factors, sociological factors and environmental factors. Teenagers motivates that doing the transvestite appear from the second motives which is the motives that can be modified, the fathers involvement in parenting  still lack that done by their father as their responsibility but still in accessibility involvement.